Solid organ transplant in recipients with ongoing SARS-CoV-2 infection: A systematic review of case reports and series - Lombardi, Andrea; Colaneri, Marta; Azzarà, Cecilia; Saltini, Paola; Viero, Giulia; Palomba, Emanuele; Biscarini, Simona; Gori, Andrea; Bandera, Alessandra (International journal of infectious diseases, 2024)
•Deliberate SOT of recipients with ongoing SARS-CoV-2 is performed worldwide.•Recipients are fit, immunized against the virus, displaying a nonsevere disease.•No COVID-19-related deaths were recorded.•The exclusion of these patients from transplantation should be reviewed. Whether solid organ transplant (SOT) can be safely performed in recipients with ongoing SARS-CoV-2 infection is still a debated question. A systematic review of the literature on recipients with ongoing SARS-CoV-2 infection at the time of surgery and the associated outcomes. From 29 studies, we identified 54 recipients; their median age was 47.5 years, and over half (23/54, 54.85%) were affected by fewer than two comorbidities. Kidney was the most common transplanted organ (24/54, 44.4%). SOT was performed without knowing the ongoing infection in 11.1% (6/54) of patients. On average, 16.1 (SD 23.2) days elapsed between SARS-CoV-2 infection and SOT, with a mean Ct value at diagnosis and transplantation of 29 and 31.9, respectively. Most patients (25/39,64.1%) had received previous COVID-19 vaccinations. Twenty-four patients (45.3%) received an anti-SARS-CoV-2 therapy. Ten patients (18.5%) required oxygen support, while seven (13.7%) were admitted to the intensive care unit. There were two reported cases (3.7%) of all-cause death, while there were no cases of COVID-19-related death. Deliberate SOT of recipients with ongoing SARS-CoV-2 is performed worldwide in candidates of nonlung transplant who are fit, immunized against the virus, and displaying a nonsevere disease course. No COVID-19-related deaths were recorded. [Display omitted]